A review modeling of optimal location and sizing integrated M–FACTS with wind farm and fuel cell. (20th September 2020) - Han, Yun; Lv, Genlai; Mokaramian, Elham
Abstract: In recent years, due to the reduction of non-renewable resources and increasing environmental pollution, exploiting of renewable energy sources is a good solution. Wind turbines and fuel cells are appropriate sources of renewable energy. On the other hand, FACTS devices are used to maximize the power injection capability to supply electricity demand and minimizing voltage deviation, power losses and operational cost of power system. Generalized Unified Power Flow Controller (GUPFC) and Interline Power Flow Controller (IPFC) are two kinds of the best FACTS devices. GUPFC can adjust the voltage and the power flow in the connected transmission lines synchronically. IPFC is capable of minimizing voltage drops and reactive power of line, enhancing the system stability against the dynamic disturbance, and load ability of the system. In this paper, with the aim of minimizing the cost function and improving the performance of system wind farm and fuel cell are integrated with power system in the presence of GUPFC and IPFC via power injection model. Then, using a new algorithm integrated with the Newton-Raphson method, the best place for installing IPFC and GUPFC is funded. This algorithm is improved squirrel search which is inspired by nature. On the other hand, the optimum range of parameter (value and angle of injected voltage) is determined with the aim of achieving the best performance of system. Ultimately, the proposed method has been applied in IEEE 57 Bus system in the presence of wind turbine, fuell cell and DG to test the effect of M-FACTS. The result confirms that the new method improved voltage profile, minimized the operational cost and power losses of system. Final, it is concluded that the performance of GUPFC is better than the IPPFC.